1985
DOI: 10.13031/2013.32311
|View full text |Cite
|
Sign up to set email alerts
|

Corn Moisture Measurement Accuracy

Abstract: The four electronic moisture meters most commonly used by Iowa grain dealers were compared with the official United States Department of Agriculture (USDA) air-oven method on 881 samples of corn from the 1979 and 1980 harvests. Samples ranged in moisture from 11% to 38%, wet basis. With the manufacturerdeveloped calibrations used in 1979, all four brands gave biased readings with respect to the air-oven method. Calibration bias errors differed among brands and ranged from approximately 1.5% to-3.5% moisture co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
1
17
0
1
Order By: Relevance
“…Test weight was associated with moisture (negatively), breakage susceptibility (negatively), and protein (positively). The test weight-moisture correlation is similar to, but much less certain, than the -0.8 reported from corn (Hall and Hill, 1973;Hurburgh et al, 1985). The negative association of test weight and breakage susceptibility means that denser kernels are generally more fracture-resistant.…”
Section: Relationships Among Soybean Quality Factorssupporting
confidence: 58%
See 1 more Smart Citation
“…Test weight was associated with moisture (negatively), breakage susceptibility (negatively), and protein (positively). The test weight-moisture correlation is similar to, but much less certain, than the -0.8 reported from corn (Hall and Hill, 1973;Hurburgh et al, 1985). The negative association of test weight and breakage susceptibility means that denser kernels are generally more fracture-resistant.…”
Section: Relationships Among Soybean Quality Factorssupporting
confidence: 58%
“…Table 2 contains a summary of the pertinent statistics relative to the NIR calibrations. For comparison, Hurburgh et al (1985) reported that electronic moisture meters have a coefficient of variation relative to oven moisture of 3 to 4%. Soybeans from 1983 and 1984 were used for the GACIII calibrations.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Accuracy of the moisture measurements required in the grain and seed trade has been achieved by continual improvement and calibration testing, but there is still some dissatisfaction with reliability in the higher moisture ranges, that is, above 20À25% for cereal grains. Recalibrations are also required occasionally because of differences in growing locations and variations in seasonal growing conditions (Hurburgh et al, 1985). An intensive study, with large numbers of samples for various grains and seed, of the variation in moisture readings due to influencing factors has been reported, and techniques were proposed Density dependence of the dielectric constant (ε 0 ) of shelled yellow-dent field corn at 24 C, 20 MHz, and indicated moisture contents (Nelson, 1979 (Funk et al, 2007).…”
Section: Moisture Content Sensingmentioning
confidence: 99%
“…There have been numerous comparisons of commercial moisture-measuring instruments in the literature. Hurburgh and co-workers [38][39] compared the four most commonly used electronic moisture meters in Iowa, USA. They included the Steinlite SS-250, the Burrows 700, the Motomco 919, and the Dickey-john GACII.…”
Section: Static Sample Moisture Measurementmentioning
confidence: 99%